Reviewing the effect of teachers’ resilience and wellbeing on their foreign language teaching enjoyment - Zhang, Linlin (Frontiers in Psychology, 2023)
This review confirms the three-factor structure of teaching enjoyment under person-context interaction, and finds that teachers' social enjoyment plays a more important role in the overall FLTE. Many prosocial interaction behaviors, such as teacher-student relationship, peer relationship, student participation and teacher support, are closely related to the classroom environment. Its prosocial situational characteristics should dominate TR and TWB in predicting FLTE. This important finding, together with the suggestion of expanding the antecedent situational variables of FLTE proposed in this review, contributes to increasing the possibility of in-depth exploration of FLTE by researchers in this field and further enriching the structure of FLTE.